TANTANGAN DAN SOLUSI DALAM PERKEMBANGAN TEKNOLOGI PENDIDIKAN DI INDONESIA - Akbar, Amin; Noviani, Nia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Educational technology in general can be interpreted as the application of technology to educational activities. The most important thing here is the process of integration between people, ideas, organizations and equipment. Based on this assumption, educational technology can be interpreted as a logical, systematic, and scientific approach to educational activities. Development of Educational Technology is currently undergoing very rapid changes, especially in the field of education. In the use of ICTs in the field of education often face several obstacles, including: the lack of procurement of ICT infrastructure in various regions, the use of used technology equipment, the lack of legal instruments in the ICT field, and the high cost of procurement and use of ICT facilities. To solve the problems mentioned above, there needs to be a solution as a condition for the successful implementation of ICT in the learning process, namely: teachers and students must have access to digital and internet technology in schools, interactive learning materials that use laptops / computers, teachers must have the ability and skills in using digital tools, there must be sufficient budget to hold, develop, and maintain facilities and infrastructure and support from all parties, principals, teachers, and students in implementing ICT learning.